Risk Disclosures pada Pelaporan Bank Pembangunan Daerah di Indonesia - Dosinta, Nina Febriana (Program Studi Akuntansi FPEB UPI, 2020)
Regional Development BanksÂ are required to innovate and anticipate changes in digitalization in the digital industry era 4.0. Financial Services Authority Â as the regulator of the Regional Development Banks developed the framework for the 2015 Regional Development Banks Transformation program which covers aspects of business and risk. Therefore, this research aims to examine whether the annual report is only a single medium for Regional Development Banks risk disclosures. This research uses a content analysis approach in Regional Development Banks reporting in Indonesia in the 2015-2019 period. The research results showed that risk disclosures are not only found in annual reports but also in sustainability reports that are separate from annual reports. This shows that Regional Development Banks not only seeks to detect the risks disclosed in the annual report but also anticipates the financial risks of sustainability disclosed in the sustainability report. Through the transformation program makes Regional Development Banks not only have high competitiveness and strong but also can contribute to the growth and equity of the regional economy.Abstrak. Bank Pembangunan Daerah (BPD) dituntut berinovasi serta mengantisipasi perubahan digitalisasi dalam era digital industri 4.0.Â Otoritas Jasa Keuangan (OJK) selaku regulator BPD menyusun kerangka kerja program Transformasi BPD tahun 2015 yang mencakup aspek bisnis dan risiko. Oleh karena itu, riset ini bertujuan untuk mengkaji apakah laporan tahunan hanya sebagai media tunggal untuk risk disclosures BPD. Riset ini menggunakan pendekatan content analysis pada pelaporan BPD di Indonesia dalam kurun waktu 2015-2019. Hasil riset menunjukkan bahwa risk disclosures tidak hanya terdapat pada laporan tahunan namun juga terdapat pada laporan keberlanjutan yang terpisah dari laporan tahunan. Hal ini menunjukkan bahwa BPD tidak hanya berupaya mendekteksi risiko yang diungkapkan dalam laporan tahunan namun juga mengantisipasi risiko keuangan keberlanjutan yang diungkapkan dalam laporan keberlanjutan. Melalui program transformasi menjadikan BPD tidak hanya memiliki daya saing yang tinggi serta kuat namun juga dapat berkontribusi pada pertumbuhan serta pemerataan ekonomi daerah.